Angiodysplasias of the colon. Issue 8 (August 1982) - Pounder, D J; Rowland, R; Pieterse, A S; Freeman, R; Hunter, R
Abstract : We studied 14 large bowel resections from patients with a provisional clinical diagnosis of a bleeding vascular lesion of the colon. For the purpose of this study we developed a barium-gelatine vascular injection technique. Six of the 14 cases were proven to be angiodysplasias with an identifiable mucosal vascular ectasia. The pathological findings in these six cases are described. We conclude that angiodysplasia represent a significant cause of lower gastrointestinal haemorrhage in the elderly. It is our opinion that only the mucosa vascular ectasia seen in these cases is histologically diagnostic and that sub-mucosal venous ectasia, while characteristic of angiodysplasia, is non-specific. the differential diagnostic features which will allow the histological distinction of angiodysplasia from other vascular lesions of the colon are discussed.